Hubungan Efikasi Diri Dengan Kepatuhan Minum Obat Pada Pasien HIV/AIDS Di RSUD Kota Tanjungpinang - Lisbet Siagian; Rizki Sari Utami; Mira Agusthia (Jurnal Rumpun Ilmu Kesehatan, 2024)
Acquired Immunodeficiency Syndrome (AIDS) is a collection of symptoms that arise due to an acquired decline in the body's immune system, caused by infection with the Human Immunodeficiency Virus (HIV). Indonesia experienced an increase in 2020, the cumulative number in Indonesia reached 911,877 HIV/AIDS cases. The cumulative number of HIV/AIDS cases in the Riau Islands reported through the SIHA report up to December 2020 was 11,436 cases. In 2021 in Tanjungpinang City, 11,356 blood samples were screened for HIV and 100 samples were found to be HIV positive. Of the 100 people who are HIV positive, 58 people have reached the AIDS stage. The aim of this research has been carried out and it is known that there is a relationship between self-efficacy and medication adherence in HIV/AIDS patients at the Tanjungpinang City Regional Hospital. This research method uses quantitative descriptive with a cross sectional approach. Data were processed using the Chi-square test. The results showed that univariate data for the high self-efficacy variable was 74.5% and low self-efficacy was 25.5%. for the medication adherence variable, the high category was 74.5% and the low category was 25.5%. The conclusion is that there is a relationship between self-efficacy and adherence to taking medication in HIV/AIDS patients at the Tanjungpinang City Regional Hospital. Recommendation: Nurses and health workers can provide more intensive education to HIV/AIDS patients about the importance of self-efficacy in undergoing treatment.